The scientific pioneer returns - Bond, Nelson S., 1908-2006; Krupa, Julian S., 1913-1989 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Scientific Pioneer Returns" by Nelson S. Bond is a science fiction narrative written in the early 20th century. The story features a mix of humor and adventure as it follows the character Lancelot Biggs, who, alongside his friend Horse-sense Hank Cleaver, navigates the perplexities of time travel and strange disappearances at Midland University. The book engages with themes of fate, the potential of scientific discovery, and the intertwining of past and future. The plot unfolds from a series of mysterious vanishings of university faculty members, leading to a frantic search by Blakeson, a publicity expert. He ultimately recruits Hank Cleaver, a seemingly simple yet remarkably insightful farmer with an uncanny knack for fixing problems. As they delve into the mystery, they face unexpected phenomena that propel them into the future aboard the space freighter, the Saturn. Characters from both the present and future clash, and they discover a malfunctioning speed accelerator has hurled them into a bizarre universe where normal physical laws are inverted. The narrative culminates in a race against time and fate as Hank devises a clever solution, ultimately saving all involved and revealing connections to future generations. (This is an automatically generated summary.)
Release date is 2024-08-10
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Time travel -- Fiction; Space ships -- Fiction